The Effect of Work Conflict, Quality of Work Life on Employee Performance with Organizational Citizenship Behavior as a Mediation Variable - Arief Lukman Hakim; Muryati; Adya Hermawati (Optima Science, 2026)
This study aims to analyze the influence of Work Conflict and Quality of Work Life on Employee Performance, with Organizational Citizenship Behavior (OCB) as a mediating variable. The study was conducted on civil servants at the Pasuruan City Regional Secretariat, with a population of all employees and a sample of 81 respondents using a saturated sampling technique. Data were analyzed using software .Smart Partial Least Square (PLS). The results of the analysis show that: (1) Work Conflict does not have a significant effect on Employee Performance, (2) Quality of Work Life also does not have a significant effect on Employee Performance, (3) Work Conflict does not have a significant effect on OCB, (4) Quality of Work Life contributes positively to increasing OCB, (5) strong OCB has a positive influence on employee performance, (6) work conflict does not have a significant influence on employee performance mediated by OCB, and (7) Quality of Work Lifeplays an important role in improving employee performance, with OCB as a mediator that strengthens the relationship. This study emphasizes the importance of Quality of Work Life in improving employee performance through OCB, although Work Conflict does not show a significant influence.